Ichthyofaunal diversity through multi-gear assessment, fishers' perception and policy review of Iloilo River, Philippines - Gaurana, Precious Nikola B. (2025.)
The Iloilo River Estuary, located in Western Visayas, Philippines, is a vital and biodiverse tropical estuary that [lays a crucial role in the economic, historical, and tourism development of Iloilo City. However, the ichthyofaunal diversity of the estuary remains largely undocumented. This study addressed this gap by providing a preliminary investigation on species composition of fish caught in the Iloilo River Estuary, while documenting the fishery practices through the perspectives of traditional fishers. Fish sampling was conducted from March to November 2022 using three different types of gear: hook and line, filter nets, and gill nets. A total of 514 fish samples were collected and subjected to morphological identification, revealing 24 species across 18 families. Among the samples, 243 individuals (47.28%) were identified as Sarotherodon melanotheron, 152 individuals (29.57%) as Megalops cy[ronoides, and 63 individuals (12.26%) as Oreochromis niloticus. The remaining 10.89% of the samples were from families Eleotridae, Carangidae, Tetraodontidae, Gobiidae, Anabantidae, Mugilidae, Serranidae,Leiognathidae, Lutjanidae, Anguillidae, Gerreidae, Sciaenidae, Scatophagidae, Latidae, and Elopidae. Fisher perception interviews and focused group discussions revealed that that at least 36 species have been caught using 13 types of fishing gears since the 1980s. Fishers identified several factors contributing to the decline in fish populations in the Iloilo River Estuary, including stocking of nonnative fish species, pollution and the decreasing depth of the river. Moreover, policy analysis showed that inadequate fisheries management may have negatively impacted fish diversity as well as led to the marginalization of traditional fishing communities in Iloilo River. This study discussed the relationship in fish diversity and implications of fisheries management strategies in Iloilo River Estuary. These findings provide essential baseline information for the effective conservation and management of the Iloilo River Estuary.
Thesis (M.S. Fisheries-Fisheries biology) -- [Miagao, Iloilo] : University of the Philippines Visayas, January 2025.
Keywords: Iloilo River estuary -- Fish diversity; Iloilo River estuary -- Conservation